1999
DOI: 10.1002/hep.510300606
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E1 protects against liver injury induced by Escherichia coli infection via a dominant th2-like response of liver T cells in mice

Abstract: Prostaglandin E series (PGEs) are known to protect against lipopolysaccharide (LPS)‐induced liver injury by down‐regulating the production of inflammatory cytokines. We show here a novel mechanism whereby prostaglandin E1 protects mice against liver injury after Escherichia coli infection. Prostaglandin E1 administration suppressed circulating interleukin 12 (IL‐12) levels but increased the IL‐10 production after E. coli challenge. Furthermore, prostaglandin E1 ‐α‐cyclodextrin (PGE1) shifted the Th1/Th2 balan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…In Leishmania infection, cells from infected mice produce more PGE 2 in BALB/c mice than in C57BL/6 mice, and the expression of COX-2 is observed in BALB/c mice, but not in C57BL/6 mice (55)(56). In a murine model of endotoxin liver injury, PGE 1 acts as a protective factor by inducing Th2 responses (57). These reports indicate that PGE 2 plays an important role in the control of diseases by regulating Th1/Th2 balance.…”
Section: Discussionmentioning
confidence: 99%
“…In Leishmania infection, cells from infected mice produce more PGE 2 in BALB/c mice than in C57BL/6 mice, and the expression of COX-2 is observed in BALB/c mice, but not in C57BL/6 mice (55)(56). In a murine model of endotoxin liver injury, PGE 1 acts as a protective factor by inducing Th2 responses (57). These reports indicate that PGE 2 plays an important role in the control of diseases by regulating Th1/Th2 balance.…”
Section: Discussionmentioning
confidence: 99%
“…Using a mouse model, recent studies reported that PGE 1 reduced ischemia-reperfusion injury following lung transplantation (de Perrot et al, 2001), collagen induced arthritis (Moriuchi-Murakami et al, 2000), and LPS-induced liver injury (Mokuno et al, 1999). In addition to the fact that PGE 1 possesses anti-inflammatory properties and the ability to modulate vascular reactivity, PGE 1 might have some beneficial therapeutic effects on IL-18-initiated diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandin E1 (PGE1), known as an antioxidant, has wide-ranging cytoprotective effects for gastrointestinal mucosa, 18 liver, 19 and kidneys. 20 Many animal experiments demonstrated that PGE1 has antiapoptotic effect on various cells, such as neuronal apoptosis in spinal cord induced by sciatic constriction injury, 21 hepatocyte apoptosis in excessive hepatectomy, 22 endothelial progenitor cell (EPC) apoptosis, 23 and renal cell apoptosis induced by cisplatin.…”
Section: Introductionmentioning
confidence: 99%